Study of prevalence and socio-demographic determinants of pterygium patients attending at a tertiary care teaching hospital of Western Maharashtra, India - Chavan, Waman M.; Kamble, Motiram G.; Giri, Purushottam A. (International Journal of Research in Medical Sciences, 2017)
Background: The pterygium is known to cause refractive errors including astigmatism, which can have negative impact on the vision. The present study was carried out to find out the prevalence and socio-demographic determinants of pterygium patients attending Pravara rural hospital, Loni, Maharashtra, India. Methods: A cross-sectional study was conducted in outpatient department of ophthalmology in Pravara rural hospital, Loni. A total of 1910 patients of various ocular morbidities were registered during the studied period in the department of ophthalmology, among these, 100 patients who had pterygium were reviewed. All 100 patients were examined by torch and slit lamp. Data were analysed statistically using percentage and proportions whenever necessary. Results: Out of the 100 pterygium patients, 48% were in the age group of >60 years, followed by 32% in the age group of 51-60 years. In relation to occupation, maximum 82% patients were farm labours followed by 11% were house workers. Majority (62%) having unilateral, while (38%) was having bilateral pterygium. All cases of pterygium were nasal. Conclusion: People who work outdoors are subjected to increase U.V. exposure. So people must be aware of this and they must take appropriate precautions like wearing protective glasses and caps etc.